Strategies of coordinated control of PSS and POD in facts for power systems (2016)
The coordinated tuning is based on the eigenvalues critical of the power system and a model reduction technique where the Hankel Singular Value method is applied. Through the linearized system model and the parameter-constrained nonlinear optimization algorithm, it can compute the parameters of both controllers. Moreover, the parameters are optimized simultaneously obtaining the gains of both controllers. On the Other hand the coordinated tuning is designed around one specific operating point, and does not guarantee robustness for different operating points and contingencies. For this reason is proposed a methodology for the computation of robust controllers that guarantee robustness in a wide range of operating condition of a power system; such as contingencies, uncertainties and delays in the signals